2013
DOI: 10.4103/1947-2714.107527
|View full text |Cite
|
Sign up to set email alerts
|

Retrowalking as an adjunct to conventional treatment versus conventional treatment alone on pain and disability in patients with acute exacerbation of chronic knee osteoarthritis: A randomized clinical trial

Abstract: Background:Increased external knee adduction moment during walking alters the joint biomechanics; which causes symptoms in chronic knee osteoarthritis patients.Aims:To assess additional effects of Retro-walking over conventional treatment on pain and disability in patients with acute exacerbation of chronic knee osteoarthritis.Materials and Methods:Thirty chronic knee osteoarthritis patients were randomly assigned into 2 groups. Group ‘A’ (7 men, 8 women) received conventional treatment. Group ‘B’ (8 men, 7 wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
29
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 5 publications
0
29
0
Order By: Relevance
“…Similarly, a recent report suggested significantly improved function after 3 weeks of retro walking in addition to the routine physiotherapy in person with knee OA [26]. Other studies reported reduced pain and disability after a combined walking program and weight training and improved postural stability following an aerobic walking and long-term weight training programs in person with knee OA [56, 57].…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Similarly, a recent report suggested significantly improved function after 3 weeks of retro walking in addition to the routine physiotherapy in person with knee OA [26]. Other studies reported reduced pain and disability after a combined walking program and weight training and improved postural stability following an aerobic walking and long-term weight training programs in person with knee OA [56, 57].…”
Section: Discussionmentioning
confidence: 95%
“…However, Loew et al [25] did not compare effects in pain and aerobic fitness level with the control group. Significant improvement in function after 3 weeks of retro walking in addition to a routine physiotherapy in person with knee OA was previously noted [26]. Moreover, a recent phase I trial indicated that 70 min walking per week was safe, feasible, and tolerated by people with severe knee OA; however, longer walking-periods may exacerbate knee pain levels [27].…”
Section: Introductionmentioning
confidence: 99%
“…Another study reported improved knee function following conventional treatment and retro-walking program in individuals with knee OA [ 25 ]. The results of the present study will enhance our understanding on the therapeutic effects of walking (retro- and forward-walking) in subjects with knee OA, and help determine whether retro- or forward-walking or both are efficacious in the management of subjects with knee OA.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, our study will assess both retro- and forward-walking program in subjects with knee OA. Previous studies were limited to pain and disability outcome measures; however, in the present study, we will assess quadriceps muscle strength and mobility, in addition to pain and disability, in subjects with knee OA [ 25 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation